When Emergency Patients Die by Suicide: The Experience of Prehospital Health Professionals - Rothes, Ines A.; Nogueira, Isabel C.; Coutinho da Silva, Ana P.; Henriques, Margarida R. (Frontiers in Psychology, 2020)
The suicide of a patient can be a disturbing experience for health professionals. According to literature, a patient suicide is a professional hazard in the path of prehospital emergency professionals. In the emergency context, several factors pointed out in literature as predictors of increased emotional impact and more severe traumatic reactions are present. However, the impact of patient suicide on prehospital emergency professionals is still an understudied subject. The aim of this study was to better understand the impact and emotional reactions of prehospital emergency professionals facing a patient suicide, using a qualitative approach. Semi-structured interviews were conducted with 19 prehospital professionals. Fourteen narratives about a patient suicide experience were obtained. Three main categories emerged from the process of content analyses: (1) emotional impact and related factors; (2) perceptions of impact; (3) emergency context and professional growing. Death by suicide in the prehospital emergency context had a considerable emotional impact on these professionals. Several participants described intrusive thoughts and images as a consequence of attending to the death scene. Regarding the perception of impact, there seemed to exist a variation between the levels of exposed to and affected by suicide. There are specific features of the prehospital emergency context that emerged in the narratives of participants as factors which increased the patient suicide impact, namely attending the death scene, encountering the family or other survivors, and managing the feeling of responsibility for not arriving in time of the rescue. The narratives of prehospital professionals also indicated some negative effects on their professional practice, such as doubts about their competence, training, and limits to liability. The death of a patient by suicide in the prehospital emergency context can be a difficult experience, marked with an intense emotional impact. Nevertheless, it can have some positive effects, such as professional growth and increased awareness for the phenomenon. Specific training appears to be fundamental to promote professional growth and to overcome the negative emotional impact.